2022
DOI: 10.3390/su14084769
|View full text |Cite
|
Sign up to set email alerts
|

Improving Older Drivers’ Behaviors Using Theory of Planned Behavior

Abstract: The proportion of older drivers has increased with the aging population. In order to improve the driving behavior and safety of older drivers, we aim to analyze behavior differences between older and younger drivers and then study an improvement strategy based on the older drivers’ behavioral characteristics. Older drivers’ behaviors can be enhanced through training, thereby improving driving safety. Simulated scenarios for behavior analysis and training are constructed for drivers who are recruited from the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The theory of planned behavior (TPB) is one of the most commonly used and influential models for studying individual behavior (Yuriev et al, 2020). To date, the TPB has been broadly used in various fields of human life, including health (Broers et al, 2020;Rajeh, 2022), environmental protection (Arya and Chaturvedi, 2020;Sun et al, 2022), tourist behavior (Japutra et al, 2019;Ulker-Demirel and Ciftci, 2020), organizational citizenship behavior Tsai et al, 2022), electronic shopping (Tang et al, 2021;Theodorou et al, 2023), and transportation (Chen, 2022;Ni et al, 2022). In terms of education, it is mainly used in innovation and entrepreneurship intention research.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The theory of planned behavior (TPB) is one of the most commonly used and influential models for studying individual behavior (Yuriev et al, 2020). To date, the TPB has been broadly used in various fields of human life, including health (Broers et al, 2020;Rajeh, 2022), environmental protection (Arya and Chaturvedi, 2020;Sun et al, 2022), tourist behavior (Japutra et al, 2019;Ulker-Demirel and Ciftci, 2020), organizational citizenship behavior Tsai et al, 2022), electronic shopping (Tang et al, 2021;Theodorou et al, 2023), and transportation (Chen, 2022;Ni et al, 2022). In terms of education, it is mainly used in innovation and entrepreneurship intention research.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It is also used to verify an assumption through linear regression [47] with factor analysis to study the observed variables through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) [28]. By considering the variables with the impacts on driver characteristics and safety in road traffic, the researchers found complex relations among the variables and [19] analyzed them with SEM by using the SPSS program to conduct EFA and AMOS program, to conduct CFA and SEM.…”
Section: Structural Equation Modelmentioning
confidence: 99%
“…The model can be used in strategic planning and accident management by responsible authorities to make further improvement in reducing the incidents in each area of the country. The study conducts literature reviews on the four dimensions by gathering and analyzing the documents as listed in Table 1 [11][12][13][14][15][16][17][18][19][20]. The literature reviews have found that a driver is influenced by the behaviors of other drivers under complex traffic situations, time pressure or at-risk events as they are causes of frustration in driving [21].…”
Section: Introductionmentioning
confidence: 99%